2011
DOI: 10.1002/jcp.22674
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid-dependent GLUT3 inhibition is a critical step for switching neuronal metabolism

Abstract: Intracellular ascorbic acid is able to modulate neuronal glucose utilization between resting and activity periods. We have previously demonstrated that intracellular ascorbic acid inhibits deoxyglucose transport in primary cultures of cortical and hippocampal neurons and in HEK293 cells. The same effect was not seen in astrocytes. Since this observation was valid only for cells expressing glucose transporter 3 (GLUT3), we evaluated the importance of this transporter on the inhibitory effect of ascorbic acid on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…The third mechanism is our own theory. We have demonstrated that neuronal intracellular ascorbic acid inhibits glucose utilization in neurons (Castro et al, 2009) through GLUT3 inhibition (Figure 8, Beltrán et al, 2011). This mechanism is supported by the idea of ascorbic acid recycling in brain (see above, Figure 10, Astuya et al, 2005).…”
Section: Neuron-glia Metabolic Couplingsupporting
confidence: 67%
“…The third mechanism is our own theory. We have demonstrated that neuronal intracellular ascorbic acid inhibits glucose utilization in neurons (Castro et al, 2009) through GLUT3 inhibition (Figure 8, Beltrán et al, 2011). This mechanism is supported by the idea of ascorbic acid recycling in brain (see above, Figure 10, Astuya et al, 2005).…”
Section: Neuron-glia Metabolic Couplingsupporting
confidence: 67%
“…The glioma cell lines (C6, ATCC ® number CCL 107™) were grown using DMEM-F12 (United States Biological, Swampscott, MA) containing 10% foetal bovine serum (FBS; HyClone, Logan, UT), 50 U/ml penicillin, 50mg/ml streptomycin, 50 ng/ml amphoreticin B, and 2 mM L-glutamine (Gibco Invitrogen Corporation, Grand Island, NY). Primary cultures: Striatal neurons were obtained from 17-day-old embryos of Wistar rats as described previously (Acuña et al, 2013, Beltrán et al, 2011). Adult female rats were anaesthetised using isoflurane (1-chloro-2,2,2-trifluoroethyl difluoromethyl ether), embryo forebrains were removed and the striatum dissected.…”
Section: Methodsmentioning
confidence: 99%
“…The fluorescence signal was normalised according to: Normalised fluorescence=normalΔnormalF/normalF=false(normalFF0false)/F0 where F 0 correspond to the mean of fluorescence intensities measured in the first 10 frames. For experiments in the presence of intracellular ascorbic acid, cells were preloaded using a solution of 1 mM ascorbic acid, for 60 min at 37 °C (Beltrán et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite efforts to define the role of glial cells in HD pathogenesis [128,129,130], or the effects that abnormal polyQ repeats have on glia [131], these aspects remain almost unattended in HD. Glial cells express huntingtin constitutively; the aggregation of mutant htt in glia induces locomotor deficits and decreases lifespan in the fly HD model [132,133].…”
Section: The Legacy Of Fly Models In Hdmentioning
confidence: 99%